2021
DOI: 10.3389/fendo.2021.608183
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of the Spinal Dorsal Horn in Diabetic Painful Neuropathy Rats With Electroacupuncture Treatment

Abstract: BackgroundClinical evidence demonstrates that electro-acupuncture (EA) of the Zu sanli (ST36) and Shen shu (BL23) acupoints is effective in relieving diabetic painful neuropathy (DPN); however, the underlying molecular mechanism requires further investigation, including the protein molecules associated with EA’s effects on DPN.MethodsSprague-Dawley adult male rats (n =36) were randomly assigned into control, DPN, and EA groups (n=12 each). After four weeks of EA treatment, response to mechanical pain and fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
8
0
4
Order By: Relevance
“…Te analgesic efect of 2 Hz EA has also been demonstrated in other pain models [54,55]. Numerous studies have shown that EA intervention on ST36 and BL60 in rats can alleviate diferent types of neuropathic pain [56][57][58]. Te preliminary study of our research group showed that the intervention of EA of ST36 and BL60 can efectively alleviate diabetic neuropathic pain [59,60].…”
Section: Discussionmentioning
confidence: 57%
“…Te analgesic efect of 2 Hz EA has also been demonstrated in other pain models [54,55]. Numerous studies have shown that EA intervention on ST36 and BL60 in rats can alleviate diferent types of neuropathic pain [56][57][58]. Te preliminary study of our research group showed that the intervention of EA of ST36 and BL60 can efectively alleviate diabetic neuropathic pain [59,60].…”
Section: Discussionmentioning
confidence: 57%
“…Atualmente 20% dos pacientes desenvolvem a DNP apresentando hiperalgesia, dor espontânea e alodinia. Com isso os especialistas perceberam que vários pacientes tinham danos na medula espinhal e passaram a utilizar animais para fazer experiências com a eletroacupuntura no corno dorsal desses animais para analisar os efeitos no tratamento da dor e na melhora da qualidade de vida desses indivíduos (Yu, et al, 2021).…”
Section: Resultsunclassified
“…Os ratos foram divididos em 3 grupos para serem avaliados: controle, DNP e EA, e para realizar os experimentos esses animais do grupo DNP e EA foram induzidos por uma injeção intraperitoneal de STZ (estreptozotocina), antibiótico que destroem as células do pâncreas causando a diabetes. No grupo da EA, os animais são presos num suporte de madeira por 14 dias após a aplicação da STZ e submetidos a eletroacupuntura em dois pontos com a estimulação de 10Hz mantida 30 minutos uma vez por dia por 4 semanas (Yu, et al, 2021).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…All methods of proteomic detection and analysis were according to our team's previous research as follows [ 21 ].…”
Section: Methodsmentioning
confidence: 99%